A novel application tunnel in combination with medical training reduces stress induced by frequent intraperitoneal injections and blood draws in mice - Anne Schlutt; Katarina Riesner; Merle Kochan; Ann-Kathrin Meß; Denise Jahn; Isabella Lurje; Wiebke Werner; Felix Heymann; Olivia Kershaw; Frank Tacke; Bernhard Hiebl; Linda Hammerich (PLoS ONE, 2026)
Handling-induced stress represents a major burden on laboratory mice and is heavily influenced by the handling technique. As such, tail-handling induces much higher stress than cup- or tunnel-handling, which is further aggravated by interventions, e.g., injections, which require even harsher fixation methods. Previous studies demonstrated that habituation protocols can improve animal welfare during handling and interventions. Here, we developed a medical training program and an alternative fixation method using an application tunnel in the context of a liver cancer model, where frequent intraperitoneal injections in male C57Bl/6 mice over many weeks are needed to induce tumor development. The training regimen consisted of 5 sessions over 2 weeks, which gradually introduced the animals to being touched by handlers and restrained for procedures. The training program was completed once before the start of any interventions, additional training sessions were performed biweekly during the entire course of the experiments. The animals were randomized to receive injections either in the novel application tunnel or using conventional fixation. Training effect was continuously monitored by measuring the latency to interact with the experimenter, the surface body temperature and by activity tracking. The latency to interact rapidly decreased during initial training sessions in both groups, and this effect was sustained throughout the course of treatment. Body temperature did not change over the course of medical training and seemed to be more influenced by environmental influences. Activity tracking demonstrated that mice injected inside the tunnel were more active and returned to their normal activity levels after injections faster than conventionally restrained mice. Those mice also showed less signs of defecation and urination during interventions. Furthermore, the tunnel had a positive influence on the well-being of mice during blood draws demonstrated by reduced signs of pain and faster willingness to interact with the handler after the procedure. In conclusion, habituation of the mice to the interventions with medical training and the improved handling procedure during ip injections and blood draws durably reduces stress levels and improves welfare of mice.